Determinants of e-commerce adoption of Philippine businesses - Francis Mark A. Quimba; Sylwyn C. Calizo (Philippine Institute for Development Studies (PIDS), 2019)
Since the late 1990s, the internet has developed as a major force in transforming how companies do their business, which led to the rapid expansion of electronic commerce, or e-commerce. In 2016, the Department of Trade and Industry adopted the Philippine E-Commerce Roadmap in recognition to the potential of e-commerce in the expansion of Philippine businesses. In support to the Philippine E-Commerce Roadmap's first success criteria having 100,000 Micro, Small, and Medium Enterprises (MSMEs) doing e-commerce, this study investigated the determinants of e-commerce adoption using the Philippine Statistics Authority's Survey of Information and Communications Technology as well as the Annual Survey of Philippine Business and Industry. The results showed that internal factors primarily determine e-commerce adoption in the Philippines. These factors include firm size, availability of computers, access to the internet, and firm use of information and communications technology (ICT) in other aspects of firm operations. Further, external factors, such as the growth rate of the industry in which the firm belongs and the market share of the firm have no statistically significant effects on e-commerce adoption. Given these results, this study recommended five actionable steps. First, bottlenecks caused by uncertainty and security concerns should be addressed. Second, government agencies need to support MSME's e-commerce adoption. Third, government agencies should assist firms in adopting ICT. Fourth, government can help provide access to finance to firms intending to adopt e-commerce. Fifth, reducing the cost and improving the quality of internet services should be pursued.
Keywords: 330; e-commerce adoption; digital economy; industry; Philippines; survey on information and communications technology; MSMEs